Treatment of biotreated palm oil mill effluent using powdered activated carbon produced from palm empty fruit bunch - Amosa, Mutiu K.; Jami, Mohammed Saedi; Al-Khatib, Ma'an Fahmi Rashid; Jimat, Dzun Noraini; Muyibi, Suleyman Aremu (2013)
Powdered Activated Carbon (PAC) was produced from empty fruit bunch (EFB) precursors by CO2 activation at 800¬0C, N2 (2.5 L/min) for 30 mins and CO2 (0.1L/min) for 15 mins. Batch adsorption was conducted using Biotreated palm oil mill effluent (BPOME) under various conditions such as agitation (100 – 200 rpm), dosage (5 – 10g) and contact time (30 – 60 mins). The maximum Chemical Oxygen Demand (COD) removal was 56.6% at the operating conditions of 10 grams, 200rpm and 30 mins contact time. Improved production conditions of PAC from EFB is expected to improve the adsorption capacity, however its availability and renewable sources indicates its prospect as a cost-effective adsorbent for industrial applications. In general, it is shown that EFB-PAC could be employed as an effective and less expensive adsorbent for the reduction of COD in BPOME. This study further supports waste to wealth and zero waste discharge policy.